Infectious endocarditis caused by Nocardia sp.: histological morphology as a guide for the specific diagnosis - Jussara Bianchi Castelli (Brazilian Journal of Infectious Diseases)
Nocardia is a rare opportunistic agent, which may affect immunocompromised individuals causing lung infections and exceptionally infective endocarditis (IE). There are few reports of IE caused by Nocardia sp., usually involving biological prostheses but rarely in natural valves. Its accurate microbiological identification may be hampered by the similarity with Rhodococcus equi and Corynebacterium spp. Here we report a case of native mitral valve IE caused by this agent in which the clinical absence of response to vancomycin and the suggestion of Nocardia sp. by histology pointed to the misdiagnosis of Corynebacterium spp. in blood cultures. The histological morphology can advise on the need for expansion of cultivation time and use of extra microbiological procedures that lead to the differential diagnosis with Corynebacterium spp. and other agents, which is essential to establish timely specific treatment, especially in immunocompromised patients.